Alteration of Epidermal Growth Factor Receptor expression following ischaemia of renal tissue - (:unkn) unknown (My University, 1999)
This study was aimed to investigate Epidermal Growth Factor Receptor (EGF-R) expression after ischaemic injury in renal tissue and the effects of calcium channel blockers in the prevention of damage due to ischaemic insult. Simple nephrectomy was performed in a group of Sprague-Dawley rats, and kidneys were grouped according to cold ischaemia time (1, 6, 12, 24 and 48 hours, respectively) and to the type of calcium channel blockers (diltiazem and verapamil) used. EGF-R expression status was investigated in each group by immunohistochemistry on paraffin sections. Overall expression of EGF-receptor was detected in 8 822.8%) kidneys. In terms of localization of EGF-receptor expression cortical tubular staining was detected in 8 (100%) kidneys, medullar tubular staining in (62.5%) kidneys and glomerular mesangial staining in 5 (62.5%) kidneys. There was no difference between various ischaemia times and different calcium channel blockers used. It has been concluded that hypoxia and cold ischaemia causes widespread down-regulation of EGF-receptor expression in renal tissue regardless of treatment with calcium channel blockers.